2018
DOI: 10.1002/lno.11086
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in coastal macrobenthic biomass and its implications for estimating secondary production using empirical models

Abstract: Macrobenthic secondary production is widely used to assess the trophic capacity, health, and functioning of marine and freshwater ecosystems. Annual production estimates are often calculated using empirical models and based on data collected during a single period of the year. Yet, many ecosystems show seasonal variations. Although ignoring seasonality may lead to biased and inaccurate estimates of annual secondary production, it has never been tested at the community level. Using time series of macrobenthic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
11
1
Order By: Relevance
“…An implicit assumption of our analysis is therefore that the ‘snapshots' of taxon biomass used to estimate production are representative of annual values. This is unlikely to be wholly accurate, and by using data from summer, when population densities and body mass tend to peak, we are likely to have overestimated annual production to some extent (Saulnier et al 2019). Nevertheless, an overestimation of annual production throughout the study area is unlikely to reduce the ability of our analysis to detect relationships between biodiversity and production, particularly as our models incorporate explanatory variables that capture seasonal change (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…An implicit assumption of our analysis is therefore that the ‘snapshots' of taxon biomass used to estimate production are representative of annual values. This is unlikely to be wholly accurate, and by using data from summer, when population densities and body mass tend to peak, we are likely to have overestimated annual production to some extent (Saulnier et al 2019). Nevertheless, an overestimation of annual production throughout the study area is unlikely to reduce the ability of our analysis to detect relationships between biodiversity and production, particularly as our models incorporate explanatory variables that capture seasonal change (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This was also beneficial for use in the semi-elastic model, as described below. The specific explanation for these log values is as follows [25][26][27][28][29].…”
Section: Descriptions Of the Variablesmentioning
confidence: 99%
“…where CR is a seasonal ratio (unitless) that converts macrobenthic biomass into mean annual biomass (estimated from Saulnier et al 2019; Supplement S3), is the total biomass observed during the survey (g AFDM), is the production-to-biomass ratio (yr -1 ) estimated using an empirical model (Brey 2012), is a regeneration coefficient (unitless) that represents somatic regeneration after sublethal predator cropping (Tableau et al 2015) and is the energy density (kJ.g AFDM -1…”
Section: Estimating Macrobenthic Food Productionmentioning
confidence: 99%
“…In temperate ecosystems, juvenile marine fish concentrate in nursery grounds from late spring to early fall, when the biomass of macrobenthic prey peaks (Beukema 1974;Saulnier et al 2019).…”
Section: Introductionmentioning
confidence: 99%